The benefits of using digital games to teach programming to children (Research, Society and Development, 2022)
A set of advantages of the inclusion of digital games in teaching-learning, shows the possibilities of being a rich tool in the construction of knowledge, making playing a learning and teaching activity, establishing the necessary objectives to achieve learning. The discussion about teaching digital games in education is not only useful. even a well designed game can have some disadvantages, for example: if it is not well executed, it loses its purpose; not all concepts can be explained through games; if the teacher intervenes frequently, he loses his playfulness; and when the student is forced to play at the insistence of the teacher, he becomes upset. In this sense, it is clear the need to analyze the national scientific production on the teaching and learning of digital game programming. In this context, this article has the general objective of analyzing the benefits of using digital games in teaching programming to children. The methodology used was a narrative literature review. It can be concluded that Computational thinking and programming practice become important allies in the development of problem solving. Learning to program affects skills related to logical and mathematical thinking, which are useful in many other learning processes and in the development of computational thinking. When teaching programming, students develop their cognitive minds because they stimulate thinking by developing game logic.